Developmental differences in relations between parent-reported executive function and unitized and non-unitized memory representations during childhood - Blankenship, Sarah L.; Riggins, Tracy (Frontiers in Psychology, 2015)
Previous research has documented an association between executive functioning (EF) and memory for bound details. However, it is unknown if this relation varies as a function of the type of bound information (i.e., unitized versus non-unitized) and whether this association changes as a function of age during childhood, when both EF and memory undergo rapid development. The current study sought to address these gaps by examining whether relations between parent-reported EF differed for unitized versus non-unitized memory representations and if these relations differed between children who were 4, 6, or 8 years of age. Results revealed that EF was selectively associated with non-unitized associative memory in 8-year-old children; no significant relations between EF and either memory condition were evident in 4- or 6-year-olds. These results suggest relations between EF and memory may be specific to non-unitized representations and that this association may emerge across childhood as both EF and memory abilities develop.